N-acetylation of 2-aminobenzothiazoles with Acetic Acid for Evaluation of Antifungal Activity and In Silico Analysis - Sukumar Bepary; Bishyajit Kumar Biswas; Prosenjit Ghosh; Md. Aminul Haque; Tran Quang De (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Acetamides (S30A1 and S30) were synthesized from benzo[d]thiazol-2-amine and 6-nitrobenzo[d]thiazol-2-amine by direct use of acetic acid instead of acetylating agents. The usual acetylating agents, acetic anhydride and acetyl chloride are very unstable especially because of their high sensitivity to environmental moisture. Thus, acetylation by direct use of acetic acid was searched as an alternative approach for synthesizing acetanilides. In this study, acetamides were synthesized with a yield of 88% and 82% respectively. The synthesized compounds were then screened for antifungal activity. At a concentration of 300 µg/disc, S30A1 showed 18 mm, 28 mm, 20 mm, and 16 mm zone of inhibitions against Penicillium notatum, Candida albicans, Aspergillus flavus, and Aspergillus niger, respectively. The standard miconazole was used at 50 µg/disc concentration. An in silico analysis was done for the possible binding modes in the C. albicans N-myristoyltransferase enzyme.